International Women's Day 2003 in Singapore : the flagship IWD event by the Singapore Council of Women's Organizations. - Kuek, Evelyn Yee Lin. (2008)
It involved the conceptualization and implementation of an International Women's Day event locally to highlight the contributions of women to Singapore's development.